The strangers - West, Jacqueline, 1979- (West, Jacqueline, 1979- Books of Elsewhere, 2013)
"When something crucial goes missing, eleven-year-old Olive and her friends must decide how to get it back--put their faith in a strange and dangerous magic, their odd new neighbors, or someone more uncertain and terrifying than both"--Provided by publisher.